The Common but Complicated Tool: Review of Embolic Materials for the Interventional Radiologist - Young, Shamar; Rostambeigi, Nassir; Golzarian, Jafar (Seminars in Interventional Radiology, 2021)
Embolization is an important and widely utilized technique in interventional radiology. There are a variety of different categories and individual products which can be utilized to perform embolization. Understanding the different classes of embolic agents, the important features of each of these classes including strengths and limitations, and the variation in individual products within the classes is critical for interventional radiologist to practice safely and effectively. This article reviews the different kinds of embolics and relays some of the pertinent physical and chemical properties of individual products which should be considered when determining which embolic to select for a given purpose.
Keywords: interventional radiology; embolization; devices; techniques